2007
DOI: 10.1007/s12011-007-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

High Accumulation of Calcium and Phosphorus in the Pineal Bodies with Aging

Abstract: To elucidate compositional changes of the pineal body with aging, the authors investigated age-related changes of elements in the pineal body. After the ordinary dissection by medical students was finished, the pineal bodies and seven arteries were resected from the subjects ranging in age from 58 to 94 years. The element contents were determined by inductively coupled plasma atomic emission spectrometry. It was found that a high accumulation of Ca and P occurred in the pineal bodies with aging. Regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…In all of the anterior commissure and corpus callosum [2] of white matter and the olfactory bulb and tract [3], pineal body [1], and mammillary body of gray matter, a significant correlation was found between Ca and Mg contents. In addition, significant correlations were found between Ca and P contents, between P and Mg contents, and between Ca and Na contents in most but not all of them.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In all of the anterior commissure and corpus callosum [2] of white matter and the olfactory bulb and tract [3], pineal body [1], and mammillary body of gray matter, a significant correlation was found between Ca and Mg contents. In addition, significant correlations were found between Ca and P contents, between P and Mg contents, and between Ca and Na contents in most but not all of them.…”
Section: Discussionmentioning
confidence: 91%
“…The authors previously investigated age-related changes of elements in the pineal body [1], corpus callosum [2], olfactory bulb and tract [3], and anterior commissure of human brain. It was found that a high accumulation of Ca and P occurred in the pineal body at old age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, significant direct correlations were found between Ca and either S or Fe contents, between Mg and either P or Fe contents, and between S and either Fe or Na contents. Table 4 shows elements with significant correlation in the anterior commissure, pineal body [24], corpus callosum [25], and olfactory bulb and tract [26]. It should be noted that Relationships between S and Fe contents (a) and between S and Na contents (b) in the anterior commissures significant correlations were found between Ca and Mg contents and between P and Mg contents in all of the anterior commissure, pineal body, corpus callosum, and olfactory bulb and tract.…”
Section: Relationship Between Fe and Na Contents In The Anterior Commmentioning
confidence: 96%